(untitled) (Journal of history-rus, 2022)
National leader, architect and founder of the independent state of Azerbaijan, world-famous politician and statesman Heydar Aliyev’s universal love and endless respect for his memory have not been bestowed on any head of state in any period of our millennial history. Heydar Aliyev is the brightest figure of the 20th century Azerbaijani politics and the architect of the 21st century independence course. His contributions to practical diplomacy will be studied for many years to come. And every time a new delicacy will be found. This process is endless. Heydar Aliyev demonstrated this to the world at a high level with his policy. In this connection, it is necessary to highlight the wisdom, restraint, determination and activity shown by the great leader in building the Baku-Tbilisi-Ceyhan oil pipeline. Even in those bloody years, the National leader always emphasized that the Baku-Ceyhan project will change the geopolitical dynamics of Eurasia as a whole. This project will make a special contribution to the development, cooperation and raising of mutually beneficial relations to a new level in a wide space. It will also make quality changes in the field of security. Experience confirmed that the Great Leader was absolutely right. Now Azerbaijan is the initiator of several important international energy and transport projects. He is an active member of the implementation of the “East-West” and “North-South” corridors, an active participant in the “New Silk Road” project. The main principles of Heydar Aliyev’s philosophy of national liberation have brought our state to a new level of development and turned it into an important geopolitical player. Of course, Heydar Aliyev’s foreign policy course played a significant role in this process. Key words: Caucasus, peace, stability, Haydar Aliyev, Azerbaijan, Armenia, politics.